Case Report: Long-term control of brain metastases with over 100 cycles of T-DM1 in HER2-positive metastatic breast cancer - Ko, Hyemi; Choi, Song-Yi; Kim, Donghyun; Lee, Jinsun (Frontiers in Oncology, 2026)
Human epidermal growth factor receptor 2 (HER2)-positive breast cancer is associated with an aggressive clinical course and a high incidence of central nervous system (CNS) metastases. Although trastuzumab emtansine (T-DM1) is a standard therapy for previously treated HER2-positive metastatic breast cancer, reports of exceptionally prolonged administration with long-term intracranial stability remain scarce. Here, we describe a patient with HER2-positive metastatic breast cancer with brain metastases who achieved long-term systemic and intracranial stability following CNS-directed local therapy and subsequent T-DM1 treatment. T-DM1 was administered from May 2019 to November 2025 (107 cycles; >6 years), and serial imaging every 3–4 months demonstrated continued disease stability without the development of new metastatic lesions. Long-term tolerability was acceptable, with only intermittent grade 1 hyperbilirubinemia without dose modification and preserved cardiac function on longitudinal monitoring. This case suggests that prolonged administration of T-DM1 may be feasible in carefully selected patients with durable clinical benefit and manageable toxicity, emphasizing the role of individualized treatment decisions, imaging surveillance, and long-term safety monitoring.